2009
DOI: 10.1017/s1368980009991820
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an integrated community-based micronutrient and health programme on anaemia in non-pregnant Malawian women

Abstract: Conclusions:The MICAH programme was an effective public health nutrition programme that was associated with significant reductions in the prevalence of anaemia among non-pregnant rural Malawian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The 21 studies included in this review [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] include data from 38 countries from Asia, Africa and Latin America ( Figure 3 ), and assess trends in anemia among WRA between 1990 and 2017. The characteristics and quality appraisal scores of the included studies, as well as the observed annualized reduction in WRA anemia, are presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 21 studies included in this review [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] include data from 38 countries from Asia, Africa and Latin America ( Figure 3 ), and assess trends in anemia among WRA between 1990 and 2017. The characteristics and quality appraisal scores of the included studies, as well as the observed annualized reduction in WRA anemia, are presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The median methodological quality score was 7 (range: 5.5–8), resulting in eight studies classified as low quality, eight studies [ 19 , 24 , 27 , 29 , 30 , 32 , 34 , 36 ] classified as moderate, and five studies [ 20 , 28 , 33 , 38 , 39 ] classified as high quality. Reduction in WRA anemia varied widely across the included studies, with CAGR ranging from −0.4 to −13.0%, with a median of −3.8%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such approaches are challenging when baseline Se intakes are low and where there is a lack of purchasing power for foods rich in Se, as in many low-income countries. Short- and medium-term policies to alleviate iron, iodine, zinc, and vitamin A deficiencies have been adopted in Malawi and elsewhere, including dietary iron supplements and salt iodisation2627, although such programmes are not used for Se. Longer-term crop-based approaches (biofortification) are also underway to increase iron, zinc and vitamin A intakes in the region2829, although the breeding potential to biofortify crops with Se via conventional breeding is low1429.…”
Section: Discussionmentioning
confidence: 99%